PENINGKATAN PROSES PEMBELAJARAN TEMATIK TERPADU MENGGUNAKAN CONTEXTUAL TEACHING AND LEARNING (CTL) DI KELAS IV SEKOLAH DASAR - YANTI, NOVA (Universitas Negeri Padang, 2014)
Abstract This research was conducted based on the facts indicating that the integrated thematic learning was not run as it was expected. The teacher seemed to ignore the involvement of the students in making correlation between the laerning materials and their real life. The purpose of this research was to describe the application of CTL approach in integrated thematic learning process. This research is a class action. This research was conducted at SD Negeri 03 Alai Kecamatan Padang Utara Kota Padang. The subject of the research was the teacher and the students of class IV totaling 27 people . The result of the research revealed that the quality of integrated thematic learning increased. The first cycle of meetings one aspect of teacher 72,22 % (C) and 63,88 %(C) of student aspects, second meeting aspect teacher 75 % (C) of the students aspect of 58,33% (D). The second cycle of meetings one aspect of teacher 83,33 % (B) of the student aspect 77,77% (B), second meeting aspect teacher 91,60 % (SB) of the students aspect 83,3% (B). Key Terms: Integrated thematic learning , CTL